PERSEPSI MAHASISWA UPBJJ-UT BANJARMASIN TERHADAP LAYANAN BANTUAN BELAJAR (TUTORIAL TATAP MUKA) - Abdul Gani, Yusran; Jumriadi, Jumriadi (Vidya Karya Jurnal Kependidikan, 2015)
The degree of learning assistance services through face-to-face tutorial presented to the university students of the Open University will bring about an impact on the height of participation of the university students in the implementation of that tutorial and in the end it will affect the learning achievement of the university students. This research is intended to know the perception of the university students of S1 PGSD UPBJJ-UT Banjarmasin toward the learning assistance services in the form of that face-to-face tutorial. This kind of research is a survey research by using the data collecting instrument in theÂ Â  form of questionnaire. The subject of the research is all the university students of S1 PGSD Classroom Teachers of the Open University (UT) within the 2014 registration period of the 1st semester, numbering 30 university students. The research result has shown that 37,25% of them are very satisfied, 62% of them are satisfied, and the remaining 0,75% of them are not satisfied with the services of face-to-face tutorial.Â